Implementasi Protokol Websocket Pada Perangkat Non IP Berbasis NRF24L01 (Studi Kasus: Sistem Monitoring Suhu dan Kontroling Lampu LED) - Labib Imam Hidayat; Adhitya Bhawiyuga; Reza Andria Siregar (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
In the current era of technology, the development of IOT (Internet of Things) Architecture has been growing very rapidly. With the increasing number of IOT devices, there are differences between the application layer protocol of the IOT devices. Which causes each devices to have their own application or can be called with the term â€œone device one appâ€. To resolve this problem, the use of web protocol to configure the entire application layer protocol or so-called WOT (Web of Things) is a great solution because of the characteristic of the web protocol which is universal. The previous concept of â€œone device one appâ€ can be changed into â€œmany device one appâ€ which means many devices can be controlled by one application. The problem that arise next is some IOT devices that require real time connections and use radio communications as a method of sending and receiving data. One of the web protocols that supports real time communication is websocket. In radio communications, many devices are used as a choice of radio communication modules. One of the most widely used radio communication module is NRF24L01. By connecting IP protocols with non-IP radio devices, it takes a bridging device that bridges the difference so that data can be transmitted properly. Therefore, the authors conduct research for the implementation of websocket protocol as a web protocol on radio or non-IP devices with case studies of controlling and monitoring systems. The testing result of the sistem is the average time for data transmission of less than one second.